Assessment of components of Gingko biloba leaves collected from different regions of China that contribute to its antioxidant effects for improved quality monitoring - LI,Li (2021)
Abstract Ginkgo biloba leaves are commonly used in traditional Chinese medicine. Owing to its wide distribution across China with varying geographical environments and climatic characteristics, G. biloba leaf products have different active ingredients and degrees of activities, which poses a challenge for quality control and standardization. We aimed to identify the key factors contributing to the quality of G. biloba based on assessment of anti-aging and antioxidative components. G. biloba leaf samples collected from 14 different regions in China were analyzed for antioxidant activities by the 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) free radical scavenging assay, and the levels of terpene lactones and flavonoids were quantified by ultra-performance liquid chromatography-tandem mass spectroscopy and high performance liquid chromatography. Correlation analysis attributed the antioxidant activity of G. biloba leaf samples of different origins to isoginkgetin and ginkgetin, which also affected the matrix metalloproteinase-1 levels of fibroblasts, determined using enzyme-linked immunosorbent assay and reverse transcription-polymerase chain reaction. Therefore, appropriate quality control of a collected G. biloba sample could be achieved by determining the levels of isoginkgetin and ginkgetin as anti-aging and antioxidant components. The results further provide a foundation for the application of G. biloba leaves as an antioxidant raw material.